2010
DOI: 10.1186/1471-2164-11-351
|View full text |Cite
|
Sign up to set email alerts
|

An initial map of chromosomal segmental copy number variations in the chicken

Abstract: BackgroundChromosomal segmental copy number variation (CNV) has been recently recognized as a very important source of genetic variability. Some CNV loci involve genes or conserved regulatory elements. Compelling evidence indicates that CNVs impact genome functions. The chicken is a very important farm animal species which has also served as a model for biological and biomedical research for hundreds of years. A map of CNVs in chickens could facilitate the identification of chromosomal regions that segregate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
106
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 65 publications
9
106
2
Order By: Relevance
“…a specific phenotype has been documented (Wright et al 2009). Intraspecific CNVs for the chicken genome were analyzed by using NimbleGen whole genome tiling arrays with 385,000 probes; the mean probe spacing was 2.6 kb (Wang et al 2010). However, the 130-kb CNV in this study was not found by them; we are, therefore, the first to report this CNV between Silky fowl and other chicken breeds.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…a specific phenotype has been documented (Wright et al 2009). Intraspecific CNVs for the chicken genome were analyzed by using NimbleGen whole genome tiling arrays with 385,000 probes; the mean probe spacing was 2.6 kb (Wang et al 2010). However, the 130-kb CNV in this study was not found by them; we are, therefore, the first to report this CNV between Silky fowl and other chicken breeds.…”
Section: Discussionmentioning
confidence: 49%
“…Furthermore, recent studies have found CNVs related to various human diseases (Wain et al 2009;Zhang et al 2009;Stankiewicz and Lupski 2010). CNVs are also observed in Aves both in inter-and intraspecies (Griffin et al 2008;Skinner et al 2009;Völker et al 2010;Wang et al 2010). In addition, an association between CNVs and Figure 3 Genetic (left) and physical (right) maps of Fm on chicken chromosome 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NGS technology and RD method employed in our work has advantages in both technology platform and genetic diversity compared with the eight previous reports [9,[32][33][34]36,[39][40][41]. Because a significant fraction of CNVs falls into genomic regions not well-covered by microarrays, especially for SD regions lacking sufficient probes [16,23], CNV as a major source of genetic variation is complementary to SNP and could account for a substantial part of missing heritability [14].…”
Section: Discussionmentioning
confidence: 78%
“…In recent years, advances in high-throughput genome scan technologies, particularly DNA hybridization on array platforms and next-generation sequencing methods, have allowed the identification of a large number of structural variants in multiple species. Although not as comprehensive as those for human, CNV maps have been produced in cattle (2,3), horse (4), sheep (5,6), pig (7), goat (8), duck (9), and chicken (10,11).…”
mentioning
confidence: 99%